Increasing Elementary School Students' Science Learning Outcomes Through Problem-Based Learning - Rudi Purwanto (Tinta Emas Publisher, 2023)
This study aims to see the impact of implementing problem-based learning in improving science learning outcomes for fifth grade students at SDN 1 Senyiur. This type of research is Classroom Action Research with 2 cycles which includes four stages, namely (a) planning, (b) implementation, (c) observation and (d) reflection. Data is collected through observation sheets, documentation, and tests in each cycle. The results showed that, on average, students' science learning outcomes had increased. In the pre-study the percentage of completeness was 50%. cycle I by 68% and cycle II by 90%. Thus it can be concluded that the application of problem-based learning can improve students' science learning outcomes. problem-based learning involves deeper thinking processes, including analysis, evaluation and decision-making based on evidence. These critical thinking skills are essential in understanding and mastering science concepts. Thus, problem-based learning is effective in improving primary school students' science learning outcomes. This learning method can increase student engagement, strengthen critical thinking skills, and present learning experiences that are relevant to everyday life. As a result of this research, it is expected that this learning approach can be further expanded in schools to improve students' science understanding more broadly